Detection of Mycoplasma ovipneumoniae from Goats with Nasal Discharge by Culture and Polymerase Chain Reaction - Ongor, Hasan; Kalin, Recep; Acik, M. Nuri (Univ Agriculture, Fac Veterinary Science, 2011)
In this study, the presence of Mycoplasma ovipneumoniae and other mycoplasmas was investigated by culture and PCR in the nasal swab samples of 692 goats with nasal discharges in 44 different flocks in eastern Turkey. The results showed that approximately 41% (18/44) of the flocks and 11% (75/692) of the goats harbored Mycoplasma agents. Among the Mycoplasma species; M. ovipneumoniae was the most prevalent species detected within 29.5% (13/44) of the flocks and 8.1% (56/692) of the goats. Mycoplasma arginini was also detected solely or in combination with M. ovipneumoniae in 18.2% (8/44) of the flocks and 1.9% (13/692) of the goats with nasal discharges. None of the samples were determined to be positive in the M. mycoides cluster and Mycoplasma agalactiae specific PCR analyses. The remaining 12 samples could not be identified at species level. Because the investigation of other agents which may cause respiratory problems such as Mannheimia was beyond the scope of this study, it is not possible to establish strong association between M. ovipneumoniae and disease. However, it may be logical to put forward that this agent might be the main cause of respiratory problems in at least three flocks in which the isolation rates of 50% or higher were obtained. (C) 2011 PVJ. All rights reserved
Keywords: Culture; Goat; Mycoplasma; ovipneumoniae; PCR